Construction of Yemilab - Park, K. S.; Kim, Y. D.; Bang, K. M.; Park, H. K.; Lee, M. H.; So, J.; Kim, S. H.; Jang, J. H.; Kim, J. H.; Kim, S. B. (Frontiers in Physics, 2024)
The Center for Underground Physics of the Institute for Basic Science (IBS) in Korea has been planning the construction of a deep underground laboratory since 2013 to search for extremely rare interactions such as dark matter and neutrinos. In September 2022, a new underground laboratory, Yemilab, was finally completed in Jeongseon, Gangwon Province, with a depth of 1,000 m and an exclusive experimental area spanning 3,000 m3. The tunnel is encased in limestone and accommodates 17 independent experimental spaces. Over 2 years, from 2023 to 2024, the Yangyang Underground Laboratory facilities will be relocated to Yemilab. Preparations are underway for the AMoRE-II, a neutrinoless double beta decay experiment, scheduled to begin in Q2 2024 at Yemilab. Additionally, Yemilab includes a cylindrical pit with a volume of approximately 6,300 m3, designed as a multipurpose laboratory for next-generation experiments involving neutrinos, dark matter, and related research. This article provides a focused overview of the construction and structure of Yemilab.